NECESIDAD DE REFORMAR EL CÓDIGO ORGÁNICO DE ORGANIZACIÓN TERRITORIAL AUTONOMÍA Y DESCENTRALIZACIÓN PARA UN EFICIENTE CUMPLIMIENTO DEL RECLAMO ADMINISTRATIVO EN LOS GAD´S - CAMPOVERDE LOJÁN, FLOR MARÍA (2016)
Abuse of administrative authority, that daily occur in the autonomous governments, it is the result of the inexplicable lack of appropriate procedure necessary to exercise our rights through the figure of administrative claim, making this issue a latent problem, affecting social, economic, legal way and direct not only the rights of citizens of Gad's administered, but to the community in general. In the Organic Code of Territorial Organization, Autonomy and Decentralization is not stipulated a specific procedure within its administrative complaint mentions regulations, and subject to the same administrative procedure, unnecessary and very general way. But within this there is no formal procedure as such for the administrative claim. The Gad's are managed by legislative acts, which should be governed by frameworks and principles established by the Constitution and other regulations. As such in the Statute of Legal and Administrative Regime of the Executive Function, has been regulated the procedure as a general guideline, so that Gad's can act according to law respecting rules and principles, the COOTAD respects the guidelines, but violates the rights to Managed by not concretely 5 specify the procedure for an efficient implementation of the administrative complaint in Los Gad's. Desconcordancia putting these two laws and infringing the rights under our Constitution. With the above it is demonstrated the need to study and need to recommend a legal proposal to reform the Organic Code of Organization Territorial Autonomy and Decentralization, in order to safeguard the interests of citizens who make up the Gad's and as such the Ecuadorian State.